Child Neglect in Namibia: Emerging Themes and Future Directions. (24th April 2019) - Sharley, Victoria; Ananias, Janetta; Rees, Alyson; Leonard, Emmerita
Abstract: This article initiates the conversation on the conceptualisation of child neglect in Namibia, reporting findings from a small study undertaken in 2017. The research is a collaboration between academics at the University of Namibia, Africa, University of Bristol and Cardiff University in the UK. The study is the first of its kind in Namibia, offering original knowledge about what constitutes neglect for children in the local context of child-rearing practice. Qualitative interviews with practitioners in schools and social-care organisations were undertaken in three of the fourteen political regions of Namibia. Interviews ascertained participants' thoughts and understandings of child neglect at individual and community levels. Teenage pregnancy and substance misuse emerged as central to the conceptualisation of neglect within the local context, with a tension between Western and indigenous child-rearing practices. This article offers rich insights into the social construction of child neglect amongst indigenous communities in Namibia, identifying a need for knowledge gathering into broader aspects of child health and well-being within Namibia's diverse indigenous peoples. The authors call for future co-produced research, which engages local communities and stakeholders in investigating this issue, to improve the health and well-being of Namibian children in congruence with the United Nations Sustainable Development Goals.